Inclusive Education and Justice for Students With Special Needs in Madrasas - Mareta, Mira; Alimah, Ade; Muhammad, Muhammad (Universitas Islam Negeri Mataram, 2024)
Inclusive education strives to provide equal opportunities for all children, regardless of their disabilities, to access education. While inclusive education is vital to ensure justice and equal opportunities for every child, the effectiveness of catering to each child's unique needs and potential is still up for debate. This article delves into research conducted in 2023 in West Nusa Tenggara, Indonesia, which explores the implementation of inclusive education and its impact on justice. The study used focus group discussions with principals, teachers, and parents of two madrasas (Islamic schools) in two regencies, the Ministry of Religious Affairs representatives, the Inclusive Madrasa Educator Forum, and a non-governmental organization. The results show that the implementation of inclusive education in madrasas has made significant progress, including an increase in the number of inclusive madrasas, positive attitudes from the school community, individualized education programs, the establishment of the Inclusive Madrasah Educator Forum, and collaboration between the government, non-government organizations, and the community. However, challenges such as limited resource allocation, a lack of teacher professional development, and obscure study plans, processes, and evaluations still exist. These unresolved challenges may lead to injustice for children with special needs in madrasas.